2023
DOI: 10.1002/smll.202303396
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Locomotion Ability of Surface Microrollers on Physiologically Relevant Microtopographical Surfaces

Ugur Bozuyuk,
Erdost Yildiz,
Mertcan Han
et al.

Abstract: Controlled microrobotic navigation inside the body possesses significant potential for various biomedical engineering applications. Successful application requires considering imaging, control, and biocompatibility. Interaction with biological environments is also a crucial factor in ensuring safe application, but can also pose counterintuitive hydrodynamic barriers, limiting the use of microrobots. Surface rolling microrobots or surface microrollers is a robust microrobotic platform with significant potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The influence of the microtopography on spherical microrollers with varying sizes was investigated through computational fluid dynamics simulations and experiments in ref. 41, revealing that the significance of the microtopography effect diminishes as the size of the microrollers increases. The three-dimensional nature of the vascular system poses an additional challenge in the movement of magnetic particles.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the microtopography on spherical microrollers with varying sizes was investigated through computational fluid dynamics simulations and experiments in ref. 41, revealing that the significance of the microtopography effect diminishes as the size of the microrollers increases. The three-dimensional nature of the vascular system poses an additional challenge in the movement of magnetic particles.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that FUS intensity values used in this study are not sufficient to evoke significant thermal or mechanical effects that might lead to stimulation of primary hippocampal neurons, especially >10 Hz neural stimulation 40 , 46 49 . In addition, we calculated the momentarily stress on the cells induced by the movement of the PEMPs on the cellular layer 50 (Supplementary Note 2 ). The calculations revealed that the forces due to propulsion of the PEMP and gravitation were <50 pN, and corresponding pressure of <50 Pa with the assumption of 1 μm 2 contact area between the PEMP and neurons.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we sought to expand the medical and pharmaceutical applications of microrollers by focusing on their biological characterizations. While past research concentrated on mi-croroller locomotion and physics, [10][11][12][13][14]73,74] we aimed to broaden their medical and pharmaceutical relevance. Our study stands out for its unique focus on combinational therapy, active magnetic targeting, and enhanced drug dissolution rates integrated into a single microroller platform.…”
Section: Discussionmentioning
confidence: 99%